Enhanced microbial electrosynthesis with three-dimensional graphene functionalized cathodes fabricated via solvothermal synthesis. (1st November 2016) - Aryal, Nabin; Halder, Arnab; Tremblay, Pier-Luc; Chi, Qijin; Zhang, Tian
Graphical abstract: Highlights: A 3D-graphene/carbon felt cathode was fabricated via solvothermal synthesis. Specific surface area of this novel electrode was increased 2 fold. The composite electrode was tested in a microbial electrosynthesis reactor. Microbial electrosynthesis of acetate from CO2 was 6.8 fold faster. Higher current consumption and biofilm density were also observed. Abstract: The biological reduction of CO2 into multicarbon chemicals can be driven by electrons derived from the cathode of a bioelectrochemical reactor via microbial electrosynthesis (MES). To increase MES productivity, conditions for optimal electron transfer between the cathode and the microbial catalyst must be implemented. Here, we report the development of a 3D-graphene functionalized carbon felt composite cathode enabling faster electron transfer to the microbial catalyst Sporomusa ovata in a MES reactor. Modification with 3D-graphene network increased the electrosynthesis rate of acetate from CO2 by 6.8 fold. It also significantly improved biofilm density and current consumption. A 2-fold increase in specific surface area of the 3D-graphene/carbon felt composite cathode explained in part the formation of more substantial biofilms compared to untreated control. Furthermore, in cyclic voltammetry analysis, 3D-graphene/carbon felt composite cathode exhibited higher current response. The results indicate that the development of a 3D-network cathode is an effective approach to improve microbe-electrode interactions leading to productive MES systems.